Targeting cancer stem cells by using the nanoparticles - Hong, In-Sun (Int J Nanomedicine, 2015)
Cancer stem cells (CSCs) have been shown to be markedly resistant to conventional cancer treatments such as chemotherapy and radiation therapy. Therefore, therapeutic strategies that selectively target CSCs will ultimately lead to better cancer treatments. Currently, accessible conventional therapeutic agents mainly eliminate the bulk tumor but do not eliminate CSCs. Therefore, the discovery and improvement of CSC-targeting therapeutic agents are necessary. Nanoparticles effectively inhibit multiple types of CSCs by targeting specific signaling pathways (Wnt/β-catenin, Notch, transforming growth factor-β, and hedgehog signaling) and/or specific markers (aldehyde dehydrogenases, CD44, CD90, and CD133) critically involved in CSC function and maintenance. In this review article, we summarized a number of findings to provide current information about their therapeutic potential of nanoparticles in various cancer cell types and CSCs.